2009
DOI: 10.1016/j.cellimm.2008.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium bovis BCG decreases MHC-II expression in vivo on murine lung macrophages and dendritic cells during aerosol infection

Abstract: Mycobacterium tuberculosis and M. bovis BCG infect APCs. In vitro, mycobacteria inhibit IFNgamma-induced MHC-II expression by macrophages, but the effects of mycobacteria on lung APCs in vivo remain unclear. To assess MHC-II expression on APCs infected in vivo, mice were aerosolinfected with GFP-expressing BCG. At 28 d, ~1% of lung APCs were GFP+ by flow cytometry and CFU data. Most GFP+ cells were CD11b high /CD11c neg-mid lung macrophages (58-68%) or CD11b high /CD11c high DCs (28-31%). Lung APC MHC-II expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 32 publications
1
45
0
1
Order By: Relevance
“…Specifically, many tumors as well rely on the induction of IL-10 and other immune suppressive cytokines to dampen type 1 immune responses and to remain immune evasive. 65 In a fashion similar to that of the tumor, although it is believed that mycobacteria may simultaneously use multiple mechanisms of immune evasion including mechanisms of down-regulating antigen presentation, 42,61 in the current study we have shown that IL-10 is one of the essential mechanisms through which the immune suppressive environment of mycobacterial granuloma is maintained. Despite the overwhelming evidence to support a direct role of mycobacterial infection in inducing IL-10 production by APCs, [37][38][39]62 it is plausible for us to consider the possibility that some level of IL-10 may be actively induced as part of host immune regulatory mechanisms as a means to limit immunopathology, a concession that could be exploited by mycobacteria and has recently been suggested by others.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Specifically, many tumors as well rely on the induction of IL-10 and other immune suppressive cytokines to dampen type 1 immune responses and to remain immune evasive. 65 In a fashion similar to that of the tumor, although it is believed that mycobacteria may simultaneously use multiple mechanisms of immune evasion including mechanisms of down-regulating antigen presentation, 42,61 in the current study we have shown that IL-10 is one of the essential mechanisms through which the immune suppressive environment of mycobacterial granuloma is maintained. Despite the overwhelming evidence to support a direct role of mycobacterial infection in inducing IL-10 production by APCs, [37][38][39]62 it is plausible for us to consider the possibility that some level of IL-10 may be actively induced as part of host immune regulatory mechanisms as a means to limit immunopathology, a concession that could be exploited by mycobacteria and has recently been suggested by others.…”
Section: Discussionmentioning
confidence: 52%
“…To address the major cellular sources displaying such type 1 immune suppression, we first analyzed the major APC populations by using purified CD11cϩ and CD11bϩ cells, which are most likely dendritic cells and macrophages, respectively. 28,42 Our data show that these CD11cϩCD11bϩ/Ϫ and CD11c-/ CD11bϩ APCs are the most prominent APC populations in both the airway lumen and granuloma (Table 1). These cells were shown to be a significant cellular source of TNF-␣, IFN-␥, IL-10, and NO in various models of pulmonary mycobacterial infection.…”
Section: Differential Pro-inflammatory and Anti-inflammatory Moleculementioning
confidence: 62%
See 1 more Smart Citation
“…Although it was initially thought that alveolar macrophages represented the major target of infection by mycobacteria, recent findings have also identified DCs as a cellular target of mycobacterial infection [3,21]. DCs have long been identified to be a major cell type involved in the delivery and presentation of antigen to naive T cells [8,29] and as such represent a critical linkage between the innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that the initiation of adaptive immunity is critically dependent on the activation of early innate immune responses. There is abundant in vitro evidence to suggest that infection by slow-growing mycobacterial species inhibits the activation of innate macrophages and DCs [21][22][23][24]. However, whether early innate immune activation is impaired in vivo following pulmonary mycobacterial infection and how this activation relates to delayed Th1-type immunity is still poorly understood.…”
mentioning
confidence: 99%